The Influence of Internal and External Factors on the Composite Stock Price Index - Antonius Nugroho Adi; Kaluge, David (Contemporary Studies in Economic, Finance and Banking, 2025)
This study aims to analyze the effect of Fundamental Ratios consisting of Return on Equity (ROE), Price to Book Value (PBV), Total Asset Turnover (TATO), Return on Asset (ROA), Return on Investment (ROI), Net Profit Margin (NPM) Firm Size and external factors consisting of inflation, interest rates, exchange rates and coal prices on stock prices in Blue Chip issuers in the energy sector. This research methodology uses a quantitative approach through purposive sampling with 10 Blue Chip issuers in the energy sector in 2017-2022. The data collected will be processed with regression analysis method using tools (E-Views) to determine the extent to which the Fundamental Ratio, Firm Size, and Factors of the Blue Chip issuers in the energy sector in 2017-2022. Fundamental Ratios, Firm Size, and External Factors affect the Share Price Share Price. The results of this study indicate that Return on Equity and Price to Book Value, Return on Invested, Net Profit Margin, Interest Rates and Coal Prices have no effect on stock prices. Total Asset Turnover, Firm Size, Return on Asset, Inflation, and Exchange Rate have a significant effect on stock pric.